Road Traffic Injuries Among Iranian Children and Adolescents: An Epidemiological Review - Salar Behzadnia; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2016)
Context: Road traffic injuries (RTIs) are the leading cause of death and globally kill 1.2 million people every year and leave 20 - 50 million people injured and disabled. In Iran, traffic related fatalities are the leading cause of death among all inadvertent fatal injuries imposed on children under five. Herein, authors review the epidemiological studies performed on vehicle accidents among Iranian children and adolescents to improve the knowledge about these preventable events. Evidence Acquisition: International databases including PubMed, Google scholar, science direct Cochrane library, and national data bases such as scientific information database (SID) were searched for terms; children, motor vehicle accident, road traffic injuries, Iran 2000 - 2015. Publication in Persian or English language related to the subject including Iranian children and adolescent's age groups were included. Among the 312 articles, 11 (two abstracts and nine full texts) were selected. Nine full texts were reviewed. Results: From 22865 victims, about 3578 children and adolescents under 19 years old were identified. Males were more affected than females. Pedestrian injury with 43.66% was the most common case of road traffic injuries. Head trauma was the most common cause of injuries reported by eight of the reviewed articles. Most of the accidents occurred between 1:00 - 6:00 PM. Most of RTIs occurred in summer. Care by emergency medical services (EMS) (29.14%) was reported by five out of the nine reviewed article. Conclusions: Most of the road traffic injuries among Iranian children and adolescents are preventable using appropriate preventive strategies such as safety facilities, safe vehicles, and safe traffic behavior, and establishing comprehensive public education programs for older children and their parents.